the profile of child malnutrition in carchi and the role of public policies - Rivera Vásquez , Jairo Israel (SATHIRI, 2022)
This work focused on the phenomenon of child malnutrition that limits early childhood development; in Ecuador, child malnutrition affects around a quarter of the population and Carchi has prevalence higher than the national average. The objective of this research was to characterize child malnutrition in Carchi, its changes over time and the role of public policies. The study methodology was mixed since it uses quantitative methods through econometric models of pooling data and qualitative methods of bibliographic review. The main result of the research was that child malnutrition in Carchi has particular characteristics towards population groups, where there have been failures in public policies.